Factors affecting recruitment to breast cancer clinical trials: an examination of the British Association of Surgical Oncology II trial and the International Breast Cancer Intervention Study - Maslin-Prothero, Sian (2000)
Breast cancer is the most common form of cancer among women in the United Kingdom, and there is considerable investment in research to identify the causes of breast cancer and the best means of diagnosis and treatments. The randomised controlled trial is the principal method used for evaluating diagnostic and treatment options. Trial organisers depend on recruitment of sufficient numbers of patients in order that the results are statistically significant and generalisable, but accrual to cancer clinical trials is poor.